2021
DOI: 10.3390/cancers13030393
|View full text |Cite
|
Sign up to set email alerts
|

Cancers in Agreement? Exploring the Cross-Talk of Cancer Metabolomic and Transcriptomic Landscapes Using Publicly Available Data

Abstract: One of the major hallmarks of cancer is the derailment of a cell’s metabolism. The multifaceted nature of cancer and different cancer types is transduced by both its transcriptomic and metabolomic landscapes. In this study, we re-purposed the publicly available transcriptomic and metabolomics data of eight cancer types (breast, lung, gastric, renal, liver, colorectal, prostate, and multiple myeloma) to find and investigate differences and commonalities on a pathway level among different cancer types. Topologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 110 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…14 17 18 It was reported that liver cancer is characterised by taurine, hypotaurine metabolism and tyrosine metabolism. 19 Glycocholic acid, glycochenodeoxycholate, taurocholate, taurochenodeoxycholate and glycolithocholic acid were reported to be the key metabolites to impact hepatic lipid accumulation and inflammation in HCC development. 15 Moreover, our portal vein metabolites results are consistent with recent studies indicating that several bile acid metabolites such as tauroursodeoxycholic Hepatology acid (TUDCA), glycochenodeoxycholate, taurocholic acid are significantly elevated in tumour tissues of patients with HCC and ICC.…”
Section: Discussionmentioning
confidence: 99%
“…14 17 18 It was reported that liver cancer is characterised by taurine, hypotaurine metabolism and tyrosine metabolism. 19 Glycocholic acid, glycochenodeoxycholate, taurocholate, taurochenodeoxycholate and glycolithocholic acid were reported to be the key metabolites to impact hepatic lipid accumulation and inflammation in HCC development. 15 Moreover, our portal vein metabolites results are consistent with recent studies indicating that several bile acid metabolites such as tauroursodeoxycholic Hepatology acid (TUDCA), glycochenodeoxycholate, taurocholic acid are significantly elevated in tumour tissues of patients with HCC and ICC.…”
Section: Discussionmentioning
confidence: 99%